High performance ocean energy harvesting turbine design–A new casing treatment scheme. (15th June 2015) - Halder, Paresh; Samad, Abdus; Kim, Jin-Hyuk; Choi, Young-Seok
Abstract: Delaying a stall improves the performance of any turbomachinery system. TC (tip clearance), which is used in a bi-directional flow Wells turbine of an ocean wave energy device, changes the flow pattern on the turbine blade suction surface, while changing or modifying the TC zone can help obtaining a delayed stall. In the present work, a new tip grooving scheme is introduced and the performance is compared for different tip groove depths and TCs of a Wells turbine. The performance is defined in terms of wider operating range or stall delay, power production and efficiency. The problem was solved by a numerical analysis technique. A multi-block meshing scheme was employed to generate structured and hexahedral elements in the computational domain and the flow was solved in ANSYS CFX ® v14.5 by solving Reynolds-averaged Navier Stokes equations. It was found that the grooves improve the turbine operating range and power production as compared to those of the turbine without a groove. The groove depth of 3% of the chord length produced highest power and widest operating range. Using the circumferential groove, 26% increase in turbine power output for a particular operating point is achieved. Highlights: A high performance wave energy turbine design philosophy is demonstrated. A new casing grooving scheme for Wells turbine for wave energy conversion is proposed. An optimal groove depth performs better in terms of operating range is reported. A comparative study of different tip clearance and grove depth is presented.